Roma Culture in Slovakia – Pedagogical and Social Reflection Research Report - Kozubík, Michal; Kwadrans, Łukasz; Michelčiková, Lenka (Wydawnictwo Naukowe UAM, 2015)
The paper is a contribution to the discussion on the possibilities and obstacles to supporting education of the Romany and their social situation through culture. Despite the fact that the Romological literature contains many scientific works or quality final research reports, there exists a blank page in the field of culture of Eastern Slovakia segregated settlements inhabitants. We humbly perceive that our explanation can raise several methodological questions. The presence itself of a non-Roma researcher in Romany society requires a description of the stay process in the field through his optics. In our case of pedagogue and social worker with a focus on Romany society, the combination of science and literary genre seemed a suitable method for drawing an image of poverty in 21st-century settlements.
Kultura romska na Słowacji – refleksje pedagogiczne i społeczne
Keywords: Roma communities; culture; social work; education